VISI MISI DAN TUJUAN DIUTUSNYA RASULULLAH SAW - Hanton (El-Rusyd, 2016)
Prophet as the messenger of Allah is very professional in every effort toward the changes he made to humanize humans, that humans walking in accordance with nature, in disseminating the vision and mission of Islam, the Qur’an and hadith as a major source of Islamic teachings already given instructions and the basic principles of education, so it should be a solution to address the educational crisis that occurred. Because it is a planned activity, education should have the clarity of vision, mission and goals to be achieved. Of us can imagine how it would be if there is an activity without having a clear vision and mission.